Structural Analysis of Toxin-Neutralizing, Single-Domain Antibodies that Bridge Ricin's A-B Subunit Interface. Issue 15 (23rd July 2021) - Rudolph, Michael J.; Poon, Amanda Y.; Kavaliauskiene, Simona; Myrann, Anne Grethe; Reynolds-Peterson, Claire; Davis, Simon A.; Sandvig, Kirsten; Vance, David J.; Mantis, Nicholas J.
Graphical abstract: Highlights: Identified single-domain antibodies (VH Hs) capable of neutralizing ricin toxin. VH Hs recognize quaternary epitopes spanning ricin's A-B subunits. VH Hs inhibit ricin attachment and limit toxin trafficking to ER. Results reveal site of vulnerability on ricin toxin and have implications for biodefense. Abstract: Ricin toxin kills mammalian cells with notorious efficiency. The toxin's B subunit (RTB) is a Gal/GalNAc-specific lectin that attaches to cell surfaces and promotes retrograde transport of ricin's A subunit (RTA) to the trans Golgi network (TGN) and endoplasmic reticulum (ER). RTA is liberated from RTB in the ER and translocated into the cell cytoplasm, where it functions as a ribosome-inactivating protein. While antibodies against ricin's individual subunits have been reported, we now describe seven alpaca-derived, single-domain antibodies (VH Hs) that span the RTA-RTB interface, including four Tier 1 VH Hs with IC50 values <1 nM. Crystal structures of each VH H bound to native ricin holotoxin revealed three different binding modes, based on contact with RTA's F-G loop (mode 1), RTB's subdomain 2γ (mode 2) or both (mode 3). VH Hs in modes 2 and 3 were highly effective at blocking ricin attachment to HeLa cells and immobilized asialofetuin, due to framework residues (FR3) that occupied the 2γ Gal/GalNAc-binding pocket and mimic ligand. The four Tier 1 VH Hs also interfered with intracellular functions of RTB, as they neutralized ricin in a post-attachment cytotoxicity assay (e.g., the toxin was bound to cell surfaces before antibody addition) and reduced the efficiency of toxin transport to the TGN. We conclude that the RTA-RTB interface is a target of potent toxin-neutralizing antibodies that interfere with both extracellular and intracellular events in ricin's cytotoxic pathway.